CONCEPTION RATE PADA SAPI KRUI DI KECAMATAN PESISIR SELATAN KABUPATEN PESISIR BARAT - Rahmat Saputra; Madi Hartono; Sri Suharyati (Department of Animal Husbandry, Faculty of Agriculture, University of Lampung, 2021)
The purpose of this research was to know the value of conception rate and the factors affecting the conception rate of Krui Cattles in Pesisir Selatan District, Pesisir Barat Regency. This research was carried out using survey method with census data collection in December 2019 until January 2020. This study used data of 166 artificially inseminated Krui cattles belong to 75 farmers and secondary data of the result of artificial insemination from two inseminators. Data was analysed using multiple regression analysis with SPSS program. The result showed that conception rate of Krui cattles at Pesisir Selatan District was 58.43%. Factors that affect conception rate were the amount of forage giving that negatively associated with factor value of 0.006, body condition score that positively associated with factor value of 0.102, and service per conception that negatively associated with factor value of 0.591. Keywords : conception rates, Krui cattles